Within- and cross-firm mobility and earnings growth - Anders Frederiksen; Timothy Halliday; Alexander K. Koch (Institute for the Study of Labor (IZA), 2010)
While it is well established that both promotions within firms and mobility across firms lead to significant earnings progression, little is known about the interaction between these types of mobility. Exploiting a large Danish panel data set and controlling for unobserved individual heterogeneity, we show that cross-firm moves at the non-executive level provide sizeable short-run gains (similar to the effect of a promotion), consistent with the existing literature. These gains, however, appear modest when compared with the persistent impact on earnings growth of promotions (either within or across firms) and subsequent mobility at a higher hierarchy level.
Keywords: C33; J6; M51; 330; earnings growth; promotions; dynamic panel data models; matched employer-employee data; Arbeitsmobilität; Erwerbsverlauf; Einkommen; Schätzung; Dänemark